1996
DOI: 10.1172/jci119020
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular inflammation induces resistance to tubular injury in the rat. A novel form of acquired, heme oxygenase-dependent resistance to renal injury.

Abstract: Considerable attention is directed to a surprising biologic phenomenon wherein tissues exposed to one insult acquire resistance to another. We identify a novel example of acquired resistance to acute renal failure and a mechanism that contributes to such resistance. Nephrotoxic serum, administered to rats 24 h before the induction of glycerol-induced acute renal failure, reduces functional and structural injury that occurs in this model. Since heme oxygenase, the ratelimiting enzyme in heme degradation, protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 50 publications
5
78
0
Order By: Relevance
“…In analogy with heat shock regulation, HO-1 overexpression in kidneys represents a critical endogenous adaptive mechanism protecting cells from stress following radiation (31), heat shock (32), inflammation (33,34), and ischemia (35). Indeed, HO-1 overexpression after gene transfer in this study prevented or significantly decreased renal injury in a stringent and clinically relevant model of 24-h cold ischemia followed by syngeneic transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…In analogy with heat shock regulation, HO-1 overexpression in kidneys represents a critical endogenous adaptive mechanism protecting cells from stress following radiation (31), heat shock (32), inflammation (33,34), and ischemia (35). Indeed, HO-1 overexpression after gene transfer in this study prevented or significantly decreased renal injury in a stringent and clinically relevant model of 24-h cold ischemia followed by syngeneic transplantation.…”
Section: Discussionmentioning
confidence: 70%
“…2 Whereas HO-1 downregulates the inflammatory response in both renal and nonrenal tissues, 18,38 repeated exposure of HO-1 Ϫ/Ϫ mice to heme proteins leads to intense interstitial cellular inflammation with significant increase in the expression of MCP-1. 39 Proximal tubular cells overexpressing HO-1 had lower MCP-1 mRNA and protein expression in response to albumin, compared with similarly treated control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Vogt et al (34) showed that exposure to nephrotoxic serum protects rats from subsequent glycerol-induced acute renal failure also thought to be due to heme oxygenase-1 expression. The protective mechanisms described in these models of renal injury were extended to accommodation by Bach et al (35), who found that accommodated grafts also express heme oxygenase-1 in addition to the antiapoptotic genes A20, Bcl-2, and Bcl-x L , whereas grafts undergoing acute vascular rejection express the proapoptotic genes Bad and Bax.…”
Section: Accommodation Of the Graftmentioning
confidence: 99%